Analysis of the use of the hate speech in social media In the case of presidential election in 2019 - Desri Wiana (English, 2019)
This study is entitled "Analysis of the Use of Hate Speech on Social Media in the Case of Presidential Election in 2019". The object of this study focused on words, phrases, and speech phrases of hate speech contained on social media Instagram and Facebook accounts in January to April 2019. The purpose of this study was to find out the use of hate speech uttered by netizens on presidential candidate pairs on Instagram and Facebook accounts, which was analyzed based on the Chief of Police's circular letter about seven speeches of hate, and identified the utterances of hatred that were more dominantly used in the social media. The research model used is qualitative research. The results of this study were derived from the speech on Instagram and Facebook social media in the 2019 presidential election. On the Instagram media, 200 sentences were analyzed in the form of hate speech, namely insulting 34 sentences or 17.5%. Denigration of 43 sentences or 21.5%. Defamation 1 sentence or 0.5%. 33. Unpleasant sentences or 16.5%. Provoke 55 sentences or 27%. Instigation numbered 21 sentences or 10.5% and spread hoaxes (Hoax) 13 sentences or 6.5%. The most dominant form of hate speech on Instagram social media is provoking. In the Facebook media, there are 200 sentences found in the form of hate speech, namely insulting 8 sentences or 4%. Denigration is 40 sentences or 20%. Defamation is 9 sentences or 4.5%. An unpleasant act of 53 sentences or 28.7%. Provoke 29 sentences or 14.5%. Instigating 61 sentences or 30.5%. and spreading hoaxes (Hoax) not found on Facebook's social media. The most dominant form of hate speech found on Facebook accounts is inciting.